Oxidative stress in soybean seedlings treated with Thymus serpyllum aqueous extract - Šućur, J.; Popović, M.; Prvulović, D.; Malenčić, Đ.; Kiprovski, B. (Biologica Nyssana, 2013)
The effect of different concentrations (0.05, 0.1 and 0.2%) of Thymus serpyllum L. aqueous extracts on lipid peroxidation process (LP), as well as reduced glutathione content (GSH) in leaves and roots of soybean seedlings were examined 24 and 72 h after the treatment. Our results showed that only highest concentration of the extract used (0.2%) enhanced process of lipid peroxidation, while concentration of 0.1% stimulated GSH accumulation in soybean seedlings.